2017
DOI: 10.3945/jn.116.241042
|View full text |Cite
|
Sign up to set email alerts
|

Combined Vitamin B-12 and Balanced Protein-Energy Supplementation Affect Homocysteine Remethylation in the Methionine Cycle in Pregnant South Indian Women of Low Vitamin B-12 Status

Abstract: Low-quality dietary protein intake and vitamin B-12 deficiency could interact to decrease methionine transmethylation and remethylation rates during pregnancy and may affect epigenetic modifications of the fetal genome. The objective of this randomized, partially open-labeled intervention trial was to examine the effect of supplemental high-quality protein and vitamin B-12 on third-trimester methionine kinetics in pregnant Indian women with a low vitamin B-12 status. Pregnant women with low serum vitamin B-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Finally, we observed no significant effect on blood cell count both at the beginning of the study (see Table 1) and after the intervention (data not shown). These results are not surprising, since our subjects were in stage 2e3 of vitamin B 12 deficiency and this condition does not affect the levels of mean corpuscular volume and hemoglobin [42].…”
Section: Discussionsupporting
confidence: 57%
“…Finally, we observed no significant effect on blood cell count both at the beginning of the study (see Table 1) and after the intervention (data not shown). These results are not surprising, since our subjects were in stage 2e3 of vitamin B 12 deficiency and this condition does not affect the levels of mean corpuscular volume and hemoglobin [42].…”
Section: Discussionsupporting
confidence: 57%
“…Evidence of higher percentage of transmethylation to methionine and reduced transculturation to cysteine were observed as a result of supplementation with both B12 and milk protein compared with only milk supplementation in women. Therefore, among Indian women presenting with low B12 in early pregnancy, supplementation with B12 and energy-protein balance plays a crucial role in enhancing the optimum function of the methionine cycle especially at the third trimester of pregnancy [118]. Similarly, B12, folate, choline and betaine-rich methyl donor supplements were used to regress the accumulation of fats in the liver induced by high-fat-sucrose probably by changing the levels of methylation of CpG areas in the promotor regions of SREBF2, estrogen receptor 1 (ESR1) and/or acylglycerol−3-Oacyltransferase−3 (AGPAT3) [96].…”
Section: Impact Of One-carbon Micronutrient Supplementation On Lipid mentioning
confidence: 99%
“…73 A combined supplementation of vitamin B12 (10 μg/day) and proteins in a balanced diet increased the homocysteine remethylation rate at the end of pregnancy. 74 The significant effect of low doses may be related to the high prevalence of vitamin deficiency in the populations studied. 10,75,76 In 100 elderly patients with serum vitamin B12 < 250 pmol/L, supplementation of 10 μg/d, 100 μg/day or 500 μg/day of cyanocobalamin for 8 weeks improved plasma vitamin B12 and MMA, urinary MMA and serum holo-TC.…”
Section: Supplementation and Food Fortificationmentioning
confidence: 99%